2016
DOI: 10.21873/anticanres.11256
|View full text |Cite
|
Sign up to set email alerts
|

Intraperitoneal Chemotherapy in Patients Pretreated for Ovarian Cancer Matched with Patients Treated with Parenteral Chemotherapy

Abstract: Our findings confirm that IPC is an effective approach compared to systemic chemotherapy for advanced ovarian cancer, even in pre-treated patients, including platinum-resistant cases. The survival benefit appears to be confined to non-heavily treated patients. Overall, direct intraperitoneal drug injection (without permanent devices) appears to be feasible, safe and possibly advantageous.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 19 publications
(30 reference statements)
0
1
0
Order By: Relevance
“…In 1985, Markman et al showed that a high dose of intraperitoneal cisplatin (200 mg/m 2 ) and intraperitoneal cytosine arabinoside in combination with systemic sodium thiosulfate was feasible and safe with a clinical response in 16 of 52 patients [ 75 ]. Moreover, a retrospective analysis showed that intraperitoneal cisplatin and intraperitoneal paclitaxel resulted in improved survival compared to standard systemic chemotherapy [ 97 ]. The authors matched 33 IP-treated patients with 66 patients who underwent systemic therapy and found a survival advantage for patients who had no more than two previous treatment lines (HR 0.21, 95% CI 0.09–0.48, p < 0.001).…”
Section: Results Of Intraperitoneal Chemotherapy For Unresectable Per...mentioning
confidence: 99%
“…In 1985, Markman et al showed that a high dose of intraperitoneal cisplatin (200 mg/m 2 ) and intraperitoneal cytosine arabinoside in combination with systemic sodium thiosulfate was feasible and safe with a clinical response in 16 of 52 patients [ 75 ]. Moreover, a retrospective analysis showed that intraperitoneal cisplatin and intraperitoneal paclitaxel resulted in improved survival compared to standard systemic chemotherapy [ 97 ]. The authors matched 33 IP-treated patients with 66 patients who underwent systemic therapy and found a survival advantage for patients who had no more than two previous treatment lines (HR 0.21, 95% CI 0.09–0.48, p < 0.001).…”
Section: Results Of Intraperitoneal Chemotherapy For Unresectable Per...mentioning
confidence: 99%